Comparative Evaluation Of Biodegradable Additives Of Ethyl Cellulose (EC) And Ethylene Vinyl Acetate (EVA) On Tribological Properties Of MBS Oil - Omar, Ghazali; Hasan, Rafidah; Masripan, Nor Azmmi; Muhammad, Noryani; A Hamid, Husna (Asian Research Publishing Network, 2020)
The effect of biodegradable additives of Ethyl cellulose (EC) and Ethylene Vinyl Acetate (EVA) on tribological properties of oil extracted from banana peel waste of Musa Aluminata Balbisiana (MBS) was evaluated. The presence of EC and EVA at difference strength of concentration leads to reduction in COF, WSD and Ws values for MBS oil. The addition of 4.0% w/w of EC and EVA in pure MBS oil at the parameter of 27 ºC and 100 N of applied load were lead to reduction in WSD and Ws. However, unlike with the COF results, addition of EC and EVA on MBS oil did not show very significant reduction either in WSD or in Ws.Therefore, they would not effectively act as anti-wear properties. It can be inferred that, at the low temperatures and strength, EC is more effectives to lead to the reduction of COF in MBS oil than EVA. Lower COF values of MBS oil with presence of additive of EC and EVA suggest that the indicative of the formation of protective tribo-chemical film, which was promoted by the tribochemical reaction due to the rubbing action and chemical interaction of EC and EVA with MBS oil. MBS oil with addition of EC showed a very stable COF value compared to the addition of EVA is reflected to the strength of the boundary film formed by the oil on the surface. Surface morphology analysis on the spherical pin used in pin on disc in tribological procedures were shown to have a predominant wear mechanisms of adhesive and abrasive wear.